ANALISIS EFESIENSI DAN PENDAPATAN USAHATANI PADI VARIETAS PANDANWANGI POLA TANAM JAJAR LEGOWO 4:1 PADA LAHAN SAWAH IRIGASI TEKNIS DI KABUPATEN BONDOWOSO - Weni Indah Doktri Agus Tapaningsih; Eko Soemarjono (Universitas Bondowoso, 2023)
The Research focused on efeciency and income of Pandanwangi Rice farming system with the legowo 4:1 cropping pattern in canals irrigation rice fields in Bondowoso Regency. The research area was chosen in Bataan Village, Tenggarang District, Bondowoso Regency. The sampling technique was total sampling, in which the number of samples was equal than population. The sample of this research was 28 respondents. The analysis used in this research was income and efficiency analysis. Based on the results, it was found that the Pandanwangi Rice farming system with the legowo 4:1 cropping pattern in canals irrigation rice fields in Bataan Village, Tenggarang District, Bondowoso Regency produced avarage income Rp. 6,000,000.-/ha and efficient.